AN ADVANCED COMPUTATIONAL APPROACH TO THE ASSESSMENT OF THE STRUCTURAL INTEGRITY OF PISTON OF INTERNAL COMBUSTION ENGINE - Mshoro, I. B. (Tanzania Journal of Engineering and Technology, 2018)
Abstract